'Living on the edge': using cognitive filters to appraise experience of environmental risk. Issue 3 (4th March 2019) - Hamilton-Webb, Alice; Naylor, Rhiannon; Manning, Louise; Conway, John
Abstract: Individuals respond to an experience of risk, both in attitudinal and behavioural terms as a result of how that experience is interpreted and appraised. Experience of local flooding can in theory, inform individuals' attitudes towards climate change. This trend however, is not observed in all cases and is highly dependent on the local, situational context. This paper postulates that the variation observed in attitudinal and behavioural responses by farmers to climate change following experiences of local flooding can, in part, be explained by the Cognitive Filters of Experience Appraisal Model introduced in this paper. The model is developed firstly through a review of the existing literature concerning appraisal (cognitive and experience). Secondly, the model is framed by empirical research via fifteen face to face interviews with farmers in Gloucestershire, England, who have all directly experienced flooding in recent years. The study is exploratory in nature, and the qualitative data serve as contextualised accounts of the different patterns of experience appraisal. The paper contributes to existing literature by developing current understandings of experience appraisal as well as providing qualitative detail to an area which has generally only been researched quantitatively. The model of experience appraisal which is put forward could be applied to multiple contexts of environmental risk.